Adding Concurrent Chemotherapy Significantly Improves the Survival of Stage II-IVb Nasopharyngeal Carcinoma Patients Treated With Concurrent Anti-EGFR Agents - Yu, Zi-Kun; Chen, Xu-Yin; Liu, Si-Han; Liu, You-Ping; You, Rui; Huang, Pei-Yu (Frontiers in Oncology, 2021)
Objective: Anti-EGFR Targeted agents were found to be capable of modulating the antitumor immunity in head and neck cancer and become more and more frequently used in the treatment of nasopharyngeal carcinoma(NPC). We aimed to explore whether adding concurrent chemotherapy influences the survival outcome of patients with stage II-IVb NPC treated with concurrent anti-EGFR agents and intensity-modulated radiation therapy (IMRT) and explore other prognostic factors for the patients. Materials and methods: A total of 656 stage II-IVb NPC patients treated with concurrent anti-EGFR agents plus IMRT between January 2011 and November 2015 were enrolled. Firstly, from these patients, a well-balanced cohort of 302 patients who received concurrent chemotherapy was created by matching potential prognostic factors. Furthermore, for all 656 stage II-IVb NPC patients, univariate and multivariate analyses of overall survival (OS), progression-free survival (PFS), locoregional recurrence-free survival (LRRFS) and distant metastasis-free survival (DMFS) were conducted to identify prognostic factors and to confirm the findings from the matching cohort. Results: Compared with concurrent anti-EGFR agents alone, combining concurrent cisplatin and anti-EGFR agents significantly improved the OS (5-year 94.7% versus 84.3%, P=0.012) and PFS (5-year 82.0% versus 71.7%, P=0.039) of NPC patients with more severe hematologic toxicity and mucositis. The independent prognostic factors identified by multivariate analysis of OS and PFS included concurrent chemotherapy, epstein-barr virus(EBV) status and clinical stage. Patients treated without induction chemotherapy (IC) may achieve more benefits from the addition of concurrent chemotherapy to concurrent anti-EGFR agents. Conclusions: For stage II-IVb NPC patients treated with concurrent anti-EGFR agents, the addition of concurrent chemotherapy can significantly improve the survival outcome.